Describing electronic, digital, and other media using AACR2 and RDA : a how-to-do-it manual and CD-ROM for librarians - Weber, Mary Beth.; Austin, Fay Angela (London : Facet, 2011)
This authoritative text is essential reading for all cataloguers, and also for information professionals and support staff using integrated library systems, searching OCLC, and applying and interpreting Library of Congress Classification and Subject Headings.
Book is accompanied by 1 computer optical disc, entitled'Describing electronic, digital, and other media using AACR2 and RDA : a how-to-do-it manual and CD-ROM for librarians bearing the same call number and available at Bahagian Koleksi Media.
Includes bibliographical references and index.
Keywords: Anglo-American cataloguing rules 2.; Resource Description and Access; Cataloging of electronic information resources; Cataloging of computer network resources; Cataloging of nonbook materials